FACTORS ASSOCIATED WITH NEONATAL HIPERBILIRUBINEMIA IN ARIFIN ACHMAD HOSPITAL PEKANBARU CITY IN 2018 (JURNAL IBU DAN ANAK, 2020)
AbstractHyperbilirubinemia is one of the clinical phenomena which most often found in newborns. More than 85% of full-term infants who are re-treatedwithin the first week of life are caused by this condition. This study aimedto determine the factors associated with the incidence ofhyperbilirubinemia in Arifin Achmad Regional Hospital Pekanbaru City in2018. This research was a descriptive analytic research with crosssectional approach conducted in August 2019 to April 2020. Thepopulation of this study were all sick babies of Arifin Achmad RegionalHospital Pekanbaru City 2018, there were totally 333 infant. Sampling inthis study was with a total sampling technique totaling 333 infants withresearch instruments using the spreadsheet. The data collection was doneby using the documentation method. Data analysis using chi squarestatistical tests with a significance level of 95%.The results showed thatthe incidence of hyperbilirubinemia in infants at Arifin Achmad PekanbaruHospital 2018 was 14.1%. Statistically there is a relationship betweenasphyxia and the incidence of hyperbilirubinemia in infants (p = 0.048),there is no relationship between Low Birth Weight (p = 0.358) and birthtrauma (p = 0.865) with the incidence of hyperbilirubinemia in infants.